Understanding seasonal variation in individual's activity participation and trip generation by using four consecutive two-week travel diary. (July 2018) - Ahmad Termida, Nursitihazlin; Susilo, Yusak O.; Franklin, Joel P.; Liu, Chengxi
Highlights: Clear trade-offs between mandatory activities and non-mandatory activities, regardless of any seasons. A positive mutual endogeneity relationship between number of trips and activity duration within the same activity type. Spring season has larger effects than any season, especially on leisure activity-travel indicators. Summer season has larger effects than any season on travel time spent for leisure activity by public transport and slow modes. Abstract: This paper explores the interactions between travel demand, time allocation and mode choice in different seasons by jointly modeling the work and/or study, routine and leisure activity-travel engagements of 67 individuals in Stockholm, Sweden. A longitudinal panel two-week travel diary data collected in four consecutive waves over a span of seven months period that covers all four different seasons; autumn, winter, spring and summer, were analysed by using simultaneous Tobit models. The model was applied to explore the interactions among each activity-travel indicator, and individuals' unique characteristics and endogeneity in activity-travel engagements between different seasons were also considered in the model system. The results of models reveal clear trade-offs between mandatory activities (work and/or study) and non-mandatory activities (routine and leisure), regardless of any seasons, although the magnitudes vary between seasons. There is also a positive mutual endogeneity relationship between number of trips and activity duration within the same activity type. The trade-offs between work and/or study trips towards routine and leisure trips are larger in winter and spring respectively, than in other seasons. It is also found that mode effects on travel time for conducting mandatory activity are much larger in spring than in other seasons. However, the effects of public transport and slow modes on travel time for leisure activities are much larger in summer than in other seasons.